2012
DOI: 10.5336/medsci.2010-21042
|View full text |Cite
|
Sign up to set email alerts
|

Cutis Tricolor Parvimaculata: A Distinct Neurocutaneous Syndrome with Brain Involvement: Case Report

Abstract: 1410utis tricolor is an entity of a neurocutaneous syndrome that must be distinguished from tuberous sclerosis and neurofibromatosis. The characteristic lesions are hypo-and hyperpigmented macules, most likely representing twin spotting, located on normal skin.1,2 The location and size of the macules are extremely variable.3,4 Thus, it is clear that cutis tricolor is not one distinct clinical entity, it should rather be taken as a cutaneous sign of several different types of mosaicism.5 Cutis tricolor parvimac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Similarly, neurological manifestations could be explained by ataxia-telangiectasia in the case report by Khumalo et al [17]. In a more recent case report [15] enlarging subcortical and periventricular mass lesions were found on cranial MRI of a 3-year-old girl with a disseminated presentation of cutis tricolor. The authors used further imaging techniques and concluded that these lesions suggested tumoral growth, but couldn't prove their diagnosis because they weren't able to biopsy the lesions owing to their location.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Similarly, neurological manifestations could be explained by ataxia-telangiectasia in the case report by Khumalo et al [17]. In a more recent case report [15] enlarging subcortical and periventricular mass lesions were found on cranial MRI of a 3-year-old girl with a disseminated presentation of cutis tricolor. The authors used further imaging techniques and concluded that these lesions suggested tumoral growth, but couldn't prove their diagnosis because they weren't able to biopsy the lesions owing to their location.…”
Section: Discussionmentioning
confidence: 72%
“…Nicita et al emphasized in their article [5] that cutis tricolor is not a single entity. It has been reported in association with various abnormalities or as an isolated cutaneous finding (Table 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]). Its coexistence with facial dysmorphism, neurological and behavioral abnormalities and skeletal dysplasia has been defined as Ruggieri-Happle syndrome [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%